Evaluations and Mechanistic Interrogation of Natural Products Isolated From Paeonia suffruticosa for the Treatment of Inflammatory Bowel Disease - Wu, Kun-Chang; Lee, Der-Yen; Hsu, Jeh-Ting; Cheng, Chi-Fang; Lan, Joung-Liang; Chiu, Shao-Chih; Cho, Der-Yang; Hsu, Jye-Lin (Frontiers in Pharmacology, 2021)
Mu Dan Pi (MDP), a traditional Chinese medicine derived from the root bark of Paeonia suffruticosa Andrews, is used to treat autoimmune diseases due to its anti-inflammatory properties. However, the impact of MDP on inflammatory bowel disease (IBD) and its principal active compounds that contribute to the anti-inflammatory properties are uncertain. Thus, this study systemically evaluated the anti-inflammatory effects of fractionated MDP, which has therapeutic potential for IBD. MDP fractions were prepared by multistep fractionation, among which the ethyl acetate-fraction MDP5 exhibited the highest potency, with anti-inflammatory activity screened by the Toll-like receptor (TLR)-2 agonist, Pam3CSK4, in a cell-based model. MDP5 (at 50 µg/ml, p < 0.001) significantly inhibited nuclear factor kappa-B (NF-κB) reporters triggered by Pam3CSK4, without significant cell toxicity. Moreover, MDP5 (at 10 µg/ml) alleviated proinflammatory signaling triggered by Pam3CSK4 in a dose-dependent manner and reduced downstream IL-6 and TNF-α production (p < 0.001) in primary macrophages. MDP5 also mitigated weight loss, clinical inflammation, colonic infiltration of immune cells and cytokine production in a murine colitis model. Index compounds including paeoniflorin derivatives (ranging from 0.1 to 3.4%), gallic acid (1.8%), and 1,2,3,4,6-penta-O-galloyl-β-D-glucose (1.1%) in MDP5 fractions were identified by LC-MS/MS and could be used as anti-inflammatory markers for MDP preparation. Collectively, these data suggest that MDP5 is a promising treatment for IBD patients.